Increasing the level of applied scientific journal "Vidnovluvana energetika" IRE NASU by switching to international criteria of scientists evaluation in the field of renewable energy use for entry into global network of scientometric database - Shchokin, A.; Ponomarenko, O. (Institute of Renewable Energy National Academy of Sciences of Ukraine, 2016)
There was formed a whole international system of scientometric databases that index different printed works, monographs, scientific journals, etc., and determine the ratings of individual scientists and editions automatically.So today publication is qualification requirements of research workers, and more important in the world takes not the fact of publication but quality. It is estimated reviewers indirectlyidentified rated periodicals in which is placed. The higher rating publication, the stricter requirements to authors and the editorial not evasive follow their application, providing the quality editions.The article provided assistance to authors for the preparation of publication materials in scientific applied magazine "Vidnovluvana energetika" IRE NASU and very important informationto improve their own level towards next awarding scientific degrees by increasing the number of citations considering the prospect of a further entry foregoing magazine in the global network of scientometric databases.